Postinfectious and sporadic functional gastrointestinal disorders have different prevalences and rates of overlap: results from a controlled cohort study 3 years after acute giardiasis. Issue 10 (18th May 2016) - Wensaas, K. A.; Hanevik, K.; Hausken, T.; Eide, G. E.; Langeland, N.; Mørch, K.; Rortveit, G.
Abstract: Background: Irritable bowel syndrome (IBS) is a common complication following gastroenteritis, and a high prevalence of postgiardiasis IBS has previously been reported. This study aims to investigate the prevalence, adjusted relative risk (RRadj), and overlap of different functional gastrointestinal disorders (FGID) according to Rome III criteria following infection with Giardia lamblia . Methods: All patients ≥18 years of age with verified giardiasis during an outbreak in 2004, and a control group matched by age and gender, were mailed a questionnaire 3 years later. Key Results: The prevalence of functional dyspepsia (FD) was 25.9% in the exposed and 6.9% in the control group, RRadj: 3.9 (95% confidence intervals [CI]: 3.1–4.8). The prevalence of IBS was 47.9% and 14.3%, respectively, with RRadj: 3.4 (95% CI: 3.0–3.8). Prevalence of other gastrointestinal symptoms ranged from 70.0% vs 39.7% for bloating (RRadj: 1.8) to 8.3% vs 2.9% for nausea (RRadj: 3.0) in the G iardia and the control group, respectively. Among individuals fulfilling criteria for IBS 44% in the exposed group and 29% in the control group also fulfilled criteria for FD. IBS subtypes based on Rome III criteria (stool consistency) showed poor agreement with subtypes based on frequency of bowel movements (Kappa‐values: 0.17 and 0.27). Conclusions & Inferences: There were high prevalences and RRs of IBS, FD and other gastrointestinal symptoms following acute giardiasis, and a high degree of overlap between the disorders. The agreement between different IBS subtype criteria varied, and there were also differences between the exposed and control group.